Understanding human security and climate change - Pink, Ross Michael 1959-; Dhofier, Luthfi (Elgar understanding series, 2024)
"In this timely work, Ross Michael Pink and Luthfi Dhofier detail specific case studies across eight countries to provide a crucial overview of the impacts of climate change. They highlight the importance of the human security paradigm, prioritising the rights of citizens rather than those of nations, to accurately assess this existential issue. Understanding Human Security and Climate Change critically analyses the climate challenges faced across North America, Africa and Asia, and their respective efforts to produce workable solutions. The threats to communities, the economy, healthcare, politics and personhood are compared, as well as the major policies and laws that have been introduced to tackle them. Each chapter contains insightful expert interviews, which contribute towards a better understanding of climate change and its consequences for humanity. This informative book is a vital resource for students and scholars of climate change, environmental policy and international relations. It is also of interest to legal practitioners, environmental policymakers and other professionals working in the environmental and human rights fields."